Morphological, molecular genetic and host plant relationship studies of rice and weed infesting populations of brown planthopper, Nilaparvata lugens (STAL) (Homoptera: Delphacidae) - Md. Abdul Latif (2000)
A total of fifteen experiments including morphological, molecular genetic and host plant relationship studies were conducted to differentiate between two sympatric populations of brown planthopper (BPH), Nilaparvata lugens, one from rice (Oryza sativa) and the other from Leersia hexandra, a weed grass. The scatter plot based on seven morphometric characters indicated that N. bakeri was totally an isolated species. Insects with high esterase activities (usually caught off rice) and those with low esterase activities (usually caught off L. hexandra) showed 6-8% overlapping between the two populations of N. lugens. But scatter plot of the morphological characters of stridulatory organs produced distributions that were almost nonoverlapping indicating that BPH with high esterase activity usually caught off rice is different from BPH with low esterase activity usually captured from L. hexandra. Scanning electron micrographs showed some variations in different morphological characters between individuals from the two sympatric populations of BPH but these were not population specific. No heterogametic mating occurred in mate choice experiments. Crosses between the two BPH populations from different host-plants showed some barriers for hybrid production. Some genetic incompatibility may exist between the two populations. After being tested for esterase activity, samples were analysed for six loci found to be polymorphic at 95% criterion namely, Mdh, Idh, Pgm, Gpi, 6Pgd and A cp . The genetic distance (average 0.182) and the existence of a diagnostic enzyme marker (GPI) between rice and Leersia infesting populations indicated that both populations are closely related but different species. The inheritance of GPI, IDH and MDH isozymes were studied in families generated from mating individuals of two sympatric populations of N lugens. These isozymes were controlled by three loci, Gpi, Mdh and Idh, respectively. These loci were inherited in simple Mendelian fashions. Thirty one bands from both short and long primer RAPD were able to be tested for segregating ratios in two families of N lugens and they were found to be inherited in simple Mendelian fashions. In the population genetic studies, two diagnostic bands, one from short primer RAPO (OP003.7; 0.6Skb) and the other from long primer RAPD (pehA#6.3; 1.00kb) were found to be present only in the Leersia infesting populations of BPH. The DPGMA cluster analyses based on both enzyme and RAPD markers showed that all the rice infesting populations of N. lugens clustered together as a group. On the other hand Leersia infesting populations of the same localities formed another distinct cluster. In host plant relationship studies, rice plants were found best suited for the establishment of the rice infesting population, and L. hexandra was a favourable host for the Leersia infesting population A consideration of the evidence from studies on host plant relationships, reproductive isolation, hybridization, morphometric variations, level of esterase activity, existence of diagnostic isozyme and DNA level markers, genetic distance, consensus tree and molecular variance between N. lugens with high esterase activity usually caught off rice and N. lugens with low esterase activity usually caught off L. hexandra suggested that both insect populations from Malaysia belong to closely related sibling species. This information has practical implications in formulating effective control measures against N. lugens which is a major pest of rice not only in Malaysia but also throughout South East Asia, South Asia and Australia